2022
DOI: 10.1186/s12951-022-01245-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from platelet-rich plasma administration in site mediate cartilage protection in subtalar osteoarthritis

Abstract: Subtalar osteoarthritis (STOA) is often secondary to chronic ankle sprains, which seriously affects the quality of life of patients. Due to its etiology and pathogenesis was not studied equivocally yet, there is currently a lack of effective conservative treatments. Although they have been used for tissue repair, platelet-rich plasma-derived exosomes (PRP-Exo) have the disadvantage of low retention and short-lived therapeutic effects. This study aimed to determine whether incorporation of PRP-Exo in thermosens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 81 publications
(93 reference statements)
0
49
0
Order By: Relevance
“…Moreover, the long-time controlled-release of pExos also could facilitate the chondrogenic differentiation of bMSCs and suppress inflammationinduced chondrocyte degeneration. (Zhang et al, 2022) 5 Advantages and challenges of exosomes in bone/cartilage tissue engineering…”
Section: Cartilage Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the long-time controlled-release of pExos also could facilitate the chondrogenic differentiation of bMSCs and suppress inflammationinduced chondrocyte degeneration. (Zhang et al, 2022) 5 Advantages and challenges of exosomes in bone/cartilage tissue engineering…”
Section: Cartilage Regenerationmentioning
confidence: 99%
“…Enhancing cartilage tissue regeneration by activating Yes-associated protein (YAP) with the Wnt signaling pathwayTao et al (2017) MSCsPromoting cartilage repair by increasing proliferation, suppressing apoptosis, and modulating immuneZhang et al (2018) Attenuating inflammation and restoring matrix homeostasis, which could relieve TMJ osteoarthritisZhang et al (2019b) Combining with AD/CS/RSF hydrogel, promoting the cell migration, proliferation, and differentiation of bMSCs, and helping the repair of cartilage defectsZhang et al (2021) Combining with Gelatin methacrylate (Gelma)/nanoclay hydrogel, containing abundant miRNA-23a-3p and promoting cartilage regenerationHu et al (2020) Platelets Incorporating the pExos into thermosensitive hydrogel for prolonging the retention time of pExos in the joint, promotong the cell proliferation and migration of bMSCs and chondrocyteZhang et al (2022) …”
mentioning
confidence: 99%
“…The main reason for loading the secretome into a hydrogel, similar to what was discussed for GFs, is to prevent the immediate washout of the active molecules and prolong therapeutic exposure seeking better effectiveness on cartilage regeneration. Many hydrogels are composed of synthetic materials which are easily handled and adjusted, present more stable biochemical properties, and are less susceptible to batch-to-batch differences [ 136 , 137 ]. A recent study has demonstrated that a mixture of Poloxamer-407 and 188 is a functional injectable carrier to deliver platelet-rich plasma-derived exosomes (PRP-Exo) in an OA model.…”
Section: Hydrogel and Cartilage Regenerationmentioning
confidence: 99%
“…The hydrogel could sustain the release of EXOs for about a month in vitro, and by using an imaging system, the authors confirmed the increase of PRP-Exo retention in the mice’s injured joint when the gel was applied. PRP-EXOs released from the hydrogel-PRP-EXOs complex remained functional, demonstrating positive effects on BM-MSC and chondrocytes in vitro and protective activity against inflammation-mediated apoptosis and degeneration of chondrocytes in vivo [ 136 ]. Another synthetic hydrogel potentially applied as a sustained-release delivery system was investigated by Tao and colleagues (2021) in OA models.…”
Section: Hydrogel and Cartilage Regenerationmentioning
confidence: 99%
“… 9 It has been reported that PRP exosomes also have protective effects on articular cartilage recently. 10 The main advantages of PRP for treatment of articular cartilage injury are simple production, high safety, minimal adverse reactions, and no foreign body rejection. 11 …”
Section: Introductionmentioning
confidence: 99%